Ni-Cr Layered Double Hydroxide/Microcrystalline Cellulose Composite as Adsorbents for Malachite Green Dye - Rotua Natalia Manalu; Zaqiya Artha Zahara; Risfidian Mohadi (Indonesian Journal of Material Research, 2023)
Malachite green dye in industrial wastewater can be removed by the adsorption method. The adsorbents used in the adsorption method were Ni-Cr LDH, microcrystalline cellulose, and Ni Cr LDH/microcrystalline cellulose composite. Regeneration process of malachite green dye with the Ni-Cr/microcrystalline cellulose adsorbent resulted in the adsorbent having the highest percent adsorbed when compared to Ni-Cr LDH and microcrystalline cellulose adsorbents. This is proof that Ni-Cr/microcrystalline cellulose LDH composite adsorbent can be used repeatedly as much as five cycles. Ni-Cr LDH material and Ni-Cr/microcrystalline cellulose LDH composite were synthesized by the coprecipitation method and were successfully carried out by XRD characterization to see the stability of the structure. The results of XRD characterization of Ni-Cr/microcrystalline cellulose composite showed peaks at diffraction angles of 11°(003), and 60°(110) which are typical regions of LDH and at diffraction angle of 22°(020) which is a typical area of microcrystalline cellulose material. Ni-Cr LDH, microcrystalline cellulose and Ni-Cr/microcrystalline cellulose get optimum pH at 7 with wavelength malachite green at 618.8 nm, kinetic equation following PSO and isotherm following Freundlich with capacity maximum until 129.870 mg.g−1. FT-IR spectra display groups found in LDH and composites including O-H, NO3−, M-O also microcrystalline cellulose have groups C-O and C-H. SEM characterization found out the biggest particle size is 1,954 µm as much as 72 and EDX composite material contains elements of O, C, Ni, Cr, Na, and N.